Pengembangan Video Animasi Fisika Sebagai Sumber Belajar Fisika Peserta Didik Pada Materi Usaha dan Energi - Alda Fauzia Kurniasari; Maria Dewati; Dasmo Dasmo (UNIVERSITAS INDRAPRASTA PGRI, 2021)
This research aims to find out the opinions of validators and the response of learners to the medium of animation video-based physics learning to increase the independence of learning developed. This research is a research and development (R&D) using the sugiono procedure. This research at WIDYA MANGGALA Jakarta High School with the research subjects are class X learners. Data collection is done with observation.instruments used in the form of questionnaires.based on validation results conducted by material expert validators and media experts obtained consecutive presentation results of 78% and 93% with very feasible criteria.